2008
DOI: 10.1111/j.1365-2133.2007.08425.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 2 is highly expressed in lesions of acne inversa and colocalizes with C-type lectin receptor

Abstract: These data indicate that the enhanced expression of TLR2 by infiltrating macrophages and DCs may contribute to the pathogenesis of inflammatory lesions of acne inversa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(125 citation statements)
references
References 25 publications
3
114
0
8
Order By: Relevance
“…Previous studies have mainly investigated the immunological responses of the skin [5,6,9] in HS as opposed to peripheral blood reflecting the systemic response. It may further be speculated that the response in the peripheral blood is related to the existence of relevant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have mainly investigated the immunological responses of the skin [5,6,9] in HS as opposed to peripheral blood reflecting the systemic response. It may further be speculated that the response in the peripheral blood is related to the existence of relevant comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that HS involves dysfunctional immune responses in both the adaptive and innate immune systems [5,6,7,8,9,10,11]. This may affect the mix of circulating leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, deficient notch signaling is able to switch the fate of outer root sheath cells, resulting in the conversion of hair follicles to keratin-enriched epidermal cysts, and compromise apocrine gland homoeostasis also leading to stimulation of toll-like receptor (TLR)-mediated innate immunity by damage-associated molecular pattern molecules released by either ruptured epidermal cysts exposing keratin fibers or altered structural components of less maintained apocrine glands, supporting and maintaining chronic inflammation. Particularly, it is believed that stimulation of TLRs on macrophages and dendritic cells (DCs), the most abundant cells in HS lesions, leads to increased amounts of proinflammatory cytokines (tumor necrosis factor [TNF]-α, interleukin [IL]-1β) and activation of DCs, which secrete IL-23 promoting Th17 cell polarization (IL-17-producing T helper cells were found to infiltrate the dermis in chronic HS lesions) [40,41,42,43,44,45,46]. Due to deficient notch signaling, impaired notch-mediated feedback inhibition of innate immunity by reduced activation of MAPK phosphatase-1 may result in chronic inflammation and Th17-driven auto-inflammation leading to progressive tissue destruction and IL-17-mediated neutrophil attraction in HS [40,41].…”
Section: Pathogenesismentioning
confidence: 99%
“…These similarities between the two disorders have led to the suggestion of acne inversa as a more appropriate description than HS [8]. Furthermore, studies have shown that similar to acne toll-like receptor 2 expression is increased in macrophages and dendritic cells of patients with HS [9]. However, there are several differences which exist between acne and HS including microbiology, clinical presentation, and response to treatment [7].…”
Section: Resultsmentioning
confidence: 99%